Linear and undulating periodized strength plus aerobic training promote similar benefits and lead to improvement of insulin resistance on obese adolescents - Inoue, Daniela Sayuri; De Mello, Marco Tulio; Foschini, Denis; Lira, Fabio Santos [UNESP]; Ganen, Aline De Piano; Da Silveira Campos, Raquel Munhoz; Sanches, Priscila De Lima; Silva, Patricia Leao; Corgosinho, Flavia Campos; Rossi, Fabricio Eduardo [UNESP]; Tufik, Sergio; Damaso, Ana R. (Elsevier B.V., 2015)
The present study compares the effectiveness of three types of physical training for obesity control in adolescents submitted to a long-term interdisciplinary therapy. Forty-five post-puberty obese adolescents (15-18yo) were randomly placed in three different groups of physical trainings: aerobic training (AT n = 20), aerobic plus strength training with linear periodization (LP n = 13) and aerobic plus strength training with daily undulating periodization (DUP n = 12). The body composition was evaluated by air-displacement plethysmography; the rest metabolic rate was measured by indirect calorimetry; serum analysis was collected after an overnight fasting. The most important finding of this study was that both LP and DUP groups improved lipid profile, insulin sensitivity and adiponectin concentration (p < 0.01). The linear regression showed a negative association between delta (%) adiponectin and delta (%) insulin (p < 0.05). Each group presented a significant reduction in body mass, body mass index and fat mass (kg) after short and long-term intervention (p < 0.01). However, the AT group reduced the fat-free mass after short-term intervention (p < 0.01) and enhanced protein oxidation (p < 0.01), whereas only LP group was able to increase the fat-free mass and maintain the rest metabolic rate (RMR). There was a negative correlation between percentage of protein oxidation and RMR (r = -0.75) in all groups. The interdisciplinary therapy models that included aerobic plus strength training were more effective than only aerobic training to improve lipid profile and insulin sensitivity, as well as the inflammatory state by increasing adiponectin. In all groups were observed an improvement on anthropometric profile. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Periodization model; Strength training; Aerobic training; Insulin resistance; Obesity